Evaluating the Ecopark Ecological Urban Area in Hung Yen Province Using the LOTUS BIO Criteria System - Xuan Duc, Do; Anh, Nguyen Quynh; Mai, Hoang Thi Ngoc; Linh, Ta Thuy; Linh, Do Khanh; Minh Hieu, Ngo; Chuc Khanh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2026)
Abstract: Selecting the appropriate set of criteria is very important in evaluating eco-urban areas that meet the standards according to green building criteria. This study aims to apply the Lotus Bio green building standard system in operation to measure the level of green building standard system compliance of eco-urban areas. We have combined mathematical models to calculate scores and establish the weights of the standard system and criteria using the Analytical Hierarchy Process (AHP) method. The study is designed to examine the level of green standard compliance, factors affecting the process of assessing the level of compliance with the LOTUS BIO green building criteria system of the Ecopark Urban Area in Hung Yen, Vietnam. The research results show that the Ecopark ecological urban area achieved lotus bio certification with 64.4/100 points. The assessment activities of green building standards of eco-urban areas should focus on ecological, health, comfort, and energy standards with corresponding scores of 4.28/6 (71.3%); 9.15/13 (70.4%), and 21.7/33 points (65.7%). The assessment activities of eco-urban areas should prioritize standards such as energy, ecology, adaptation, and mitigation with high weights (weights: 0.24; 0.10, and 0.09). In each standard, the assessment should prioritize criteria with high weight values such as energy consumption intensity (0.52), sustainable water use solutions (0.32), healthy shopping (0.54), vegetation (0.49), solid waste management (0.34), occupant comfort (0.21), green transportation (0.42), support for people with disabilities to access and use (0.42), acceptance, operation, trial run (0.46), outstanding performance (0.55). The method of assessing ecological urban areas using the Lotus Bio green building standards can be applied to other ecological urban areas.